2014
DOI: 10.3989/revmetalm.028
|View full text |Cite
|
Sign up to set email alerts
|

Basic research on mechanism of BN inclusion in improving the machinability of steel

Abstract: Boron nitride-added eco-friendly free cutting steel has recently drawn more and more attention. But, the mechanisms explaining the role of BN inclusions improving the machinability of steels is not very clear. In this investigation, the material removal mechanism for cutting of BN inclusions in steels is explored, using a combination of theoretical analysis and a series of experiments. First, the actual shape of BN inclusions is observed and the amount and distribution of BN inclusions is quantitatively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The use of boron nitride (BN) also demonstrated enhanced machinability in austenitic stainless steels [9] and heat-treatable steels [10,11]. Chen et al showed the potential benefits of using both manganese sulfides (MnS) and boron nitride (BN) simultaneously to improve machinability [12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of boron nitride (BN) also demonstrated enhanced machinability in austenitic stainless steels [9] and heat-treatable steels [10,11]. Chen et al showed the potential benefits of using both manganese sulfides (MnS) and boron nitride (BN) simultaneously to improve machinability [12].…”
Section: Introductionmentioning
confidence: 99%